Utilization of Oyster Shell Powder for Hydration and Mechanical Properties Improvement of Portland Cement Pastes - Darweesh, H. H. M. (Journal of Sustainable Materials Processing and Management, 2023)
Supplementary cementitious materials (SCMs) are usually partially substitueted at the expense of Portland cement (OPC) to reduce as possible the CO2 emmision. There has been limited studies invoved the use of Oyster shell (OS) to replace OPC. The current study investigated the properties of a ternary base batch containing Oyster shell powder (OSP). The ternary cement batch was consisting of OPC, granulated blast furnace slag (GbfS) and metakaolin (MK). The results indicated that the water of consistency and setting times (initial and final) are gradually increased. The water absorption and total porosity are decreased, while the bulk density and combined water content increased. This behaviour continued up till 16 % OSP content, but then the reverse was obtained with any further increase of OSP content. The same trend was achieved with the compressive strength. The addition of OSP often formed mono- and/or hemicarbonate instead of monosulfate because it is mainly composed of carbonates, and moreover it is stabilizing the formation of trisulphate or ettringite in the hydrated samples. The decrease of free lime contents proved that the OSP is a pozzolanic material. This was confirmed by FT-IR spectra. The optimum content of OSP was at most 16 %.